Moderating Role Of Organizational Culture On The Effect Of Paternalistic Leadership On Hotels’ Employee Work Engagement In The Eastern Part Of Indonesia - S.P WENEHENUBUN; V.H. VANESA; D. SHANTY; Triyani TRIYANI; H.H. SILALAHI; Y. HARTIJASTI (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to examine the moderating role of organizational culture on the effect of paternalistic leadership on employee work engagement in the Eastern part of Indonesia. A simple random sampling technique was used. Using an online questionnaire via Google Forms, data was collected from 169 respondents which consisted of staff to manager level at 14 hotels in the Eastern part of Indonesia. This study used structural equation modeling (SEM) to analyze the relationship. The result reveals that in Eastern Part of Indonesia, paternalistic leadership does not affect on employee work engagement. Likewise, the moderating role of organizational culture does not completely have a positive effect on paternalistic leadership and work engagement. The results of this research indicate that theoretically, the PL style can only be applied in organizations that focus more on administrative or management. This research only focuses on hotel business organizations in the Eastern part of Indonesia and does not involve other business units. In addition, this study only uses quantitative methods with online questionnaires. Further research should involve many hotels throughout The Eastern part of Indonesia, including the more comprehensive business unit. It is also necessary to use the interview method to ensure the quality of the research results.